MicroRNA-29b/graphene oxide–polyethyleneglycol–polyethylenimine complex incorporated within chitosan hydrogel promotes osteogenesis - Qin, Han; Ji, Yujie; Li, Guangyue; Xu, Xiaohui; Zhang, Chuangwei; Zhong, Wenjie; Xu, Shihan; Yin, Yuanyuan; Song, Jinlin (Frontiers in Chemistry, 2022)
MicroRNAs (miRNAs) play a pivotal role in regulating a number of physiologic and pathologic processes including bone marrow mesenchymal stem cell (BMSC) osteogenic differentiation, making them a candidate used to promote osteogenesis. However, due to intrinsic structure and characteristics, “naked” miRNAs are unstable in serum and could not pass across the cellular membrane. Nano delivery systems seem to be a solution to these issues. Recently, graphene oxide (GO)-based nanomaterials are considered to be promising for gene delivery due to their unique physiochemical characteristics such as high surface area, biocompatibility, and easy modification. In this work, a GO-based nanocomplex functionalized by polyethyleneglycol (PEG) and polyethylenimine (PEI) was prepared for loading and delivering miR-29b, which participates in multiple steps of bone formation. The nanocomplex revealed good biocompatibility, miRNA loading capacity, and transfection efficiency. The miR-29b/GO-PEG-PEI nanocomplex was capsulated into chitosan (CS) hydrogel for osteogenesis. In vitro and in vivo evaluation indicated that miR-29b/GO-PEG-PEI@CS composite hydrogel was able to promote BMSC osteogenic differentiation and bone regeneration. All these results indicate that PEG/PEI functionalized GO could serve as a promising candidate for miRNA cellular delivery, and the miR-29b/GO-PEG-PEI@CS hydrogel has the potential for repairing bone defects in vivo.